Hate Speech in the Information Society: something heinous that erodes the image rights of the human person - Cavalcanti, Ana Elizabeth (2021)
This work aims to reflect on the hate speech and the personality rights focusing on the right to image in the context of The Information Society. For the development of this research, it was necessary to analyze the liberty of expression as a right and how its exercise impacts the behavior of our society, even the possibility of violations of individual rights such as the right to image. The research methodology adopted was the deductive, starting from the study of legislation, doctrine and jurisprudence in the field of the Brazilian legal system that deals with the personality rights and individual rights, taking as an example, the right of image, obtaining as a result the indicative that hate speech can be considered as a mechanism for the violation of rights and that they are enforced by the use of new technologies in the current Information Society. In conclusion, it comes to the idea that the expressions of the minority human personalities, who are in vulnerability, in the face of a computerized society that we currently deal with, are frontally violated by hat speech that, in turn, must be stopped so that individual rights can be protected.